Achromobacter xylosoxidans Infection Following Total Knee Arthroplasty - Lee, Su Chan; Nam, Chang Hyun; Park, Il Seok; Yoon, Ji Yeol; Jung, Kwang Am; Hwang, Seung Hyun (The journal of the Korean Orthopaedic Association, 2014)
Achromobacter xylosoxidans is an opportunistic organism, mainly causing infection in immune compromised hosts, such as patients on dialysis. However, review of the medical literature showed that few cases of A. xylosoxidans infections following total knee arthroplasty have been reported. This organism has not been reported in prosthetic joint infections of patients who are not immune compromised. Here, a case of periprosthetic infection with A. xylosoxidans following total knee arthroplasty in a man with no medical history of immune suppression is reported. KCI Citation Count: 0